Mycobacterium leprae Induces Neutrophilic Degranulation and Low-Density Neutrophil Generation During Erythema Nodosum Leprosum - Tavares, Isabella Forasteiro; dos Santos, Jessica Brandão; Pacheco, Fabiana dos Santos; Gandini, Mariana; Mariante, Rafael M.; Rodrigues, Thais Fernanda; Sales, Anna Maria; Moraes, Milton Ozório; Sarno, Euzenir Nunes; Schmitz, Veronica (Frontiers in Medicine, 2021)
Erythema Nodosum Leprosum (ENL) is a recurrent acute inflammatory complication of leprosy affecting up to 50% of all Borderline Lepromatous and Lepromatous Leprosy (BL/LL) patients. Although ENL is described as an immune reaction mediated by neutrophils, studies demonstrating the direct role of neutrophils in ENL are still rare. One subpopulation of low-density neutrophils (LDNs), present within the fraction of peripheral blood mononuclear cells (PBMC), has been associated with the pathogenesis and severity of diseases like sepsis, lupus, and tuberculosis. We herein analyzed LDNs and high-density neutrophils (HDNs) in terms of frequency, phenotype, and morphology. Serum levels of MMP-9 (a neutrophilic degranulation marker) were evaluated by ELISA; and LDNs were generated in vitro by stimulating healthy-donor, whole-blood cultures. PBMC layers of ENL patients presented segmented/hypersegmented cells that were morphologically compatible with neutrophils. Immunofluorescence analyses identified LDNs in ENL. Flow cytometry confirmed the elevated frequency of circulating LDNs (CD14-CD15+) in ENL patients compared to healthy donors and nonreactional Borderline Tuberculoid (BT) patients. Moreover, flow cytometry analyses revealed that ENL LDNs had a neutrophilic-activated phenotype. ENL patients under thalidomide treatment presented similar frequency of LDNs as observed before treatment but its activation status was lower. In addition, Mycobacterium leprae induced in vitro generation of LDNs in whole blood in a dose-dependent fashion; and TGF-, an inhibitor of neutrophilic degranulation, prevented LDNs generation. MMP-9 serum levels of BL/LL patients with or without ENL correlated with LDNs frequency at the same time that ultrastructural observations of ENL LDNs showed suggestive signs of degranulation. Together, our data provide new insights into the knowledge and understanding of the pathogenesis of ENL while enriching the role of neutrophils in leprosy.